Promotion of development of high tech agricultural zones in Vietnam: status and solutions - Hoa, Tran Ngoc (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
Development of agriculture with application of high technologies (called afterwards as “high tech agriculture”) is seen as a solution for Vietnam agriculture development in context of agricultural structure shift, international integration and response to disasters and climate changes. The actual development of high tech agriculture in USA, Netherlands, Thailand, China, Israel and other countries shows that these countries achieve record harvest values, namely 250-300 ton/ha of tomato harvest, 100-150 ton/ha of grapefruit harvest (10 times higher than traditional cultivation) and 1.5 million of flower twigs/ha. High tech agriculture cultivation gives an average value of USD120,000-150,000/ha per year in Israel or a value of USD40,000-50,000/ha per year in China (40-50 times higher than traditional cultivation). These figures are illustrations of efficiency of this trend of development with high tech agriculture models, high tech agriculture zones and incubators of firms. In this paper, the author deals with development of high tech agriculture zones which are taken as core component for development of high tech agriculture of Vietnam. The author shows the actual status of development of this sector as well as shortcomings and, at the same time, makes a recommendation of measures for settlement of difficulties and development of high techs. Code: 19051001 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">